Critical Influences on Child Language Acquisition and Development - Messer, David J. author. aut Link
XXV, 278 p.
Keywords: The book identifies and assesses the importance of a range of influences on child language acquisition and development, paying particular attention to situational influences. Key issues are highlighted and recent research is succinctly presented. There are five sections: the deployment of speech during early development; linguistic interaction and family background: encoding the situation; multidimentional aspects of language development; and constraints on language development. There are twelve chapters on these themes contributed by leading researchers in this area.